Collaborative Action Pursuits within EFL Task- Based Peer Interactions - Kadriye AKSOY-PEKACAR; İsmail Hakki ERTEN (Anı Publishing, 2021)
This study aimed to unveil collaborative actions in EFL task-based peer interactions. Collaboration in peer interaction has been mainly investigated by analysing language-related episodes (LREs). Assuming that an etic coding would limit the understanding of collaborative actions, a qualitative analysis of learner interactions, particularly sociocultural discourse analysis, was adopted for this study. The data include 11 hours of peer interactions collected from a speaking club designed as an extracurricular activity. The participants were 15 adult learners enrolled at a language school of a Turkish state university and they were informed to have B1+ proficiency level. The learners were grouped into three groups and assigned to complete two language tasks: divergent and convergent tasks in L2. The interactions were recorded, and by employing the constant comparative method, all the collaborative actions were identified in the data. Two broad categories of collaborative actions emerged; languagerelated and task-related, each of which has different subcategories. In this paper, the language-related collaborative actions, which are eight in total, are defined and exemplified with extracts from the data. The results present implications for the inclusion of peer interaction activities, especially in EFL contexts where learners have limited opportunities in participating in L2 interaction.